Multimedia Data Mining: A Systematic Introduction to Concepts and Theory - Zhang, Zhongfei (CRC Press, 2009)
Multimedia data mining is a growing research field of interest to researchers in a wide range of disciplines. Multimedia Data Mining: A Systematic Introduction to Concepts and Theory describes the fundamental theory and techniques used in multimedia data mining research and practice. The book covers statistical mining theory and methods, soft-computing-based mining theory and methods, and graph-based mining theory and methods. The authors also discuss in detail the applications of these techniques in various modalities of multimedia data, including imagery, video, and audio. In addition, the book provides a website with supplementary information.